Optimization Of Container Stacking Productivity At East Kalimantan Container Port Using Swot Method - Muhammad Khaisar Wirawan; Nurul Hidayah; Destyariani Liana Putri (Maritime Park: Journal of Maritime Technology and Society, 2025)
Based on the PM Perhubungan, the dwelling time limit at the Port is 3 days, in fact the stacking of containers at the Container Port lasts more than 3 days and causes the stacking of containers to be less than optimal and productive. This study aims to provide recommendations for strategies to optimize the productivity of container stacking at the Container Port. The analysis of this research strategy uses a SWOT analysis which produces the type of recommended strategy for the Container Port is the WT (Weakness-Threats) strategy consisting ofimproving supporting facilities for container stacking services, increasing stacking rates, and improving the quality of human resources through training.